2008
DOI: 10.2176/nmc.48.140
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic Spinal Epidural Abscess Caused by Salmonella Typhi -Case Report-

Abstract: A 56-year-old man presented with a rare spinal epidural abscess manifesting as attacks of back pain associated with fever, weight loss, generalized weakness and fatigability, and constipation. He had multiple skin pustules in the last 4 months treated with oral amoxicillin. He had suffered diabetes mellitus for the last 5 years and was insulin dependent. Physical examination found slight paraparesis with sensory loss around the nipple and sphincteric urgency, and diabetic retinopathy. Magnetic resonance imagin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…Ampicillin, trimethoprim-sulfamethoxazole and third generation cephalosporins, can be used for resistant cases, in children and in those who cannot tolerate fluoroquinolones 4. Hence, it is imperative to assess drug sensitivity and adjust the treatment regimen accordingly 9. Surgical debridement may be necessary for cases with abscess formation, as in our case.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Ampicillin, trimethoprim-sulfamethoxazole and third generation cephalosporins, can be used for resistant cases, in children and in those who cannot tolerate fluoroquinolones 4. Hence, it is imperative to assess drug sensitivity and adjust the treatment regimen accordingly 9. Surgical debridement may be necessary for cases with abscess formation, as in our case.…”
Section: Discussionmentioning
confidence: 92%
“…Until now, fluoroquinolones have been considered the drug of choice for the treatment of enteric fever. However, resistance to this class of antibiotic, especially with S. typhi and S. paratyphi , in south-east Asia, the Middle East and Africa, has become a serious matter of concern 8 9. Ampicillin, trimethoprim-sulfamethoxazole and third generation cephalosporins, can be used for resistant cases, in children and in those who cannot tolerate fluoroquinolones 4.…”
Section: Discussionmentioning
confidence: 99%
“…Various authors have reported the rare occurrence of salmonella osteomyelitis involving the spine in immunocompetent patients (Ozturk et al, 2006;Santos and Sapico, 1998;Carvell and MacLarnon, 1981;Dolan et al, 1987;Hunt et al, 1996;Hunt, 1965;Le, 1982;Miller et al, 1988;Mnaymneh, 1977;O'Keeffe et al, 1978;Ortiz-Neu et al, 1978;Sapico and Montgomerie, 1979;Schweitzer et al, 1971;Govender et al, 1999;Cottalorda et al, 1997;Abdullah et al, 2008;Acharya and Bhatnagar, 2004;Akagi et al, 1998). From these groups a few have reported surgical intervention (Ozturk et al, 2006;Wu et al, 2004;Hunt et al, 1996;Le, 1982;Mnaymneh, 1977;Abdullah et al, 2008;Acharya and Bhatnagar, 2004;Akagi et al, 1998) for the treatment of the infection (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…From these groups a few have reported surgical intervention (Ozturk et al, 2006;Wu et al, 2004;Hunt et al, 1996;Le, 1982;Mnaymneh, 1977;Abdullah et al, 2008;Acharya and Bhatnagar, 2004;Akagi et al, 1998) for the treatment of the infection (Table 1). None of these case reports though, provides a possible explanation for this incidence.…”
Section: Resultsmentioning
confidence: 99%
“…It is responsible for variety of human illnesses ranging from gastroenteritis, typhoid fever, and bacteremia to the asymptomatic carrier state [2]. Infection of a spinal segment with paravertebral abscess due to Salmonella has been reported to be extremely rare and that too in patients with predisposing factors such as sickle cell anemia, corticosteroid therapy, and malignancies [3,4]. Since the incidence of tubercular infection of the spine is very high in the Indian subcontinent, it leads to a high index of suspicion and institution of empirical treatment for the same.…”
Section: Introductionmentioning
confidence: 99%